Optimalisasi Pengelolaan Sampah Organik di Kelurahan Balongsari melalui Pemberdayaan Masyarakat dengan Metode Kompos Takakura - Siska Tri Karisma Dewi; Meirina Ernawati; Errisa Dwiani (Yayasan Literasi Sains Indonesia, 2024)
The majority of waste produced by residents in the Balongsari Subdistrict is organic waste from household activities. The waste problem becomes more complex if public awareness about the importance of waste management remains low. To address this, Balongsari Subdistrict authorities and officials RW 4, 5, and 6, along with the community service team, agreed to conduct a waste management socialization activity using the Takakura method, targeting the PKK Mobilization Team. This activity aims to increase community knowledge and skills in managing kitchen waste, revive the community's enthusiasm for composting waste, and reduce waste volume. The method used is a participatory approach involving socialization, education, demonstrations, and hands-on practice with residents to create compost using the Takakura method. The results show that this community service activity improved residents' awareness and skills in converting household waste into compost. The increased active participation of 26 participants and the commitment of 85% of participants to implement the Takakura method at home demonstrate the success of this activity. The Takakura method offers an effective solution for reducing organic waste volume and producing high-quality compost. This practical introduction hopes to encourage more efficient and environmentally friendly waste management practices at the household level.